Peran Pemeriksaan Kesehatan Preventif (Skrining) Gratis Dalam Mengurangi Beban Ekonomi Penyakit Di Indonesia - Rahmawati; Abustan Nur; Hijrah Hijrah; Stevania Fitri; Sucianti Sucianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The economic burden of disease is a major challenge in the Indonesian health system, primarily due to the increasing prevalence of non-communicable diseases that require long-term healthcare costs. One strategy developed to reduce this burden is free preventive health checks (screening) through a promotive and preventive approach. This study aims to examine the role of free preventive health checks (screening) in reducing the economic burden of disease in Indonesia. The research method used was a literature review by examining national and international scientific articles published in the last five years (2020–2025). The literature search was conducted through Google Scholar, GARUDA, and PubMed databases with keywords related to health screening, economic burden of disease, and health economics. Data analysis used descriptive analysis and narrative synthesis. The results of the study indicate that free health screening plays a role in increasing early disease detection, reducing the cost of further treatment, reducing hospitalization rates, and reducing productivity losses due to chronic diseases. In addition, free screening also improves public access to health services, especially for low-income groups. Thus, free preventive health checks (screening) can be seen as a strategic and cost-effective health investment in supporting the control of the economic burden of disease and national health development in Indonesia.